IMPORTANCE OF RELIGIOUS AND CONFESSIONAL DISTANCE IN THE SHAPING OF STUDENTS’ IDENTITY IN KOSOVO & METOHIJA (Религиски дијалог и соработка, 2021)
Starting from the assumption that religious identificationhas increased its significance in the shaping of identity in theenvironments which have been in the ambience of “frozen conflict”on a long-term basis, the extent of significance ascribed to it bystudents in Kosovo & Metohija has been examined. It is assumedthat, independently of how the students themselves identifyregarding religion, and of the place of religious identification inthe identity matrix, they manifest significant distance towards thereligiously “other” because it is the area with the politicizationof the church and religious feelings, whereas religion becomesa means, an instrument of empowering national identity. Theimportance of religious affiliation as an identity segment of thesurveyed population has been seen through the comparison of selfassessments of the importance of a series of identity markers (boththose regarding traditional identity structures such as national,religious and family affiliation, and the markers typical of modernidentity, such as sub-cultural, professional and regional affiliation).Religious/confessional distance was examined on the Bogardusscale, adapted to the examined student population. The researchwas conducted by the survey technique in December 2016/January2017 on the proportional quota sample of 997 students of theAlbanian University in Priština and the Serbian state University in Kosovska Mitrovica. The research was aimed at measuring thevalue of religious/confessional distance of the students at theseuniversities and exploring the importance of religion/confession inthe structure of their identity.